2018
DOI: 10.1080/17290376.2018.1455603
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role played by parents, culture and the school curriculum in socializing young women on sexual health issues in rural South African communities

Abstract: Background: the decline in South Africa’s HIV infection rates especially among young women is encouraging. However, studies show that the 15–24-year-old cohort remains vulnerable. As they still report early sexual debut, being involved in sexual partnerships with older men as well as having unprotected sex. These risky sexual behaviors may be linked to factors such as the parent–child sexual health communication and the timing of the first talk. The quality of sexual health information received in school may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
1
34
0
5
Order By: Relevance
“…The findings confirm the importance of considering the quality of the parent-child relationship when considering involving parents in addressing adolescent sexual risk behaviour. A child who feels that her parents are interested in and understand her problems (connectedness) is more likely to seek advice and guidance about important sensitive issues, such as sex [54]. Indeed, this has been demonstrated in a South Africa study, which showed that when the parent-child relationship was strengthened, it also increased the frequency of parent-child communication about HIV/AIDS and sexuality issues [55].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The findings confirm the importance of considering the quality of the parent-child relationship when considering involving parents in addressing adolescent sexual risk behaviour. A child who feels that her parents are interested in and understand her problems (connectedness) is more likely to seek advice and guidance about important sensitive issues, such as sex [54]. Indeed, this has been demonstrated in a South Africa study, which showed that when the parent-child relationship was strengthened, it also increased the frequency of parent-child communication about HIV/AIDS and sexuality issues [55].…”
Section: Discussionmentioning
confidence: 96%
“…These studies found that parents tend to believe that girls who are in school do not have sex and thus do not need information about it [20]. Parents were also more likely to speak to their children about sex when they are older, reach puberty/menses and/or when parents suspect they have romantic relationships and exhibit signs of engaging in sexual behaviour [35,37,54]. However, as suggested by the formative studies conducted for the RISE project [62], it is also possible that out of school girls in rural Zambia perceive themselves as adults who are ready for marriage and therefore are less hesitant to speak to their parents about sexual issues.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a recent study by Ahmed et al 2018, low social support, gender norms, and HIV stigma were among other factors why people from low-and middle-income countries would not discuss or initiate treatment of HIV/AIDS. Mpondo et al (2018), in a study they conducted in South Africa, found that parent-child communication on sexual health matters in rural communities was limited to messages that warned against pregnancy, while the messages were also fraught with cultural idioms that could be difficult to comprehend because of their ambiguous meanings. These findings also confirm the findings of our study that sociocultural and demographic factors influenced discussion of HIV/AIDS and SRH issues between Nigerian parents and their children.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, parents play a critical role in the socialization of their children, of which sexuality is critical. Mpondo et al (2018) buttress this reality when they say that "sexual health communication that is provided by the parents is considered very important," This fact is further corroborated by Soon et al, when they explained that parents play important roles in influencing adolescent sexual decision-making and access to information about HIV and general SRH issues (Soon et al, 2013).…”
Section: The Roles Of Parents In the Communication Of Hiv/aids And Srmentioning
confidence: 91%
See 1 more Smart Citation